ANALISIS PINJAMAN DAERAH DALAM PEMBIAYAAN PEMBANGUNAN PADA DAERAH KABUPATEN HALMAHERA UTARA - Arifin, Putri Dewi Annira; Syahdan, Rinto; Sinen, Kasim (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
The research aims to determine the long-term debt repayment capacity of North Halmahera Regency and determine the ability of North Halmahera Regency to finance development 2018-2022. The research results show (1) The financial condition of the North Halmahera Regency Government is quite good because seen from 2018-2021, the North Halmahera Regency Government does not have short-term, medium-term and long-term loans. However, in 2022, the North Halmahera Regency government's finances will experience a deficit due to expenditure that is greater than the income received by the region. (2) DSCR analysis in 2022 show a value of -76,980, which means that North Halmahera Regency has not been able to repay the loan principal and interest. because it is less than 2.5. (3) The Regional Government of North Halmahera Regency during the 2018-2022 budget year does not have short or medium term loans. The only loans owned are long-term loans in 2022 which will be used to cover the budget deficit and to finance activities in the form of providing public service facilities and infrastructure. (4) The financial performance of the Regional Government of North Halmahera Regency is measured by the ratio of the degree of fiscal decentralization during the 2018 to fiscal years. By 2022 the average percentage obtained is 10.03% on a scale of 10.01-20.00% with the criteria of poor regional financial capacity.